Isolation and characterization of cellulose degrading bacteria from faeces of ruminants - Castueras, Melvi Joy N.; Farinas, Donna Rose B. (2013)
The increasing amount of cellulosic materials accumulating in the environment has led to researchers on microorganism producing enzymes capable of degrading cellulose into glucose monomers that may be used for many industrial applications. The microbial system found in an animal's faeces is one of the most used sources for the isolation of cellulose-degrading bacteria. This present study performed the isolation, characterization, and determination of the cellulose activity of cellulolytic bacteria found in faeces of ruminants, specially from carabao, deer, horse, sheep and hebra, collected from Manila Zoo. Thirteen aerobic cellulose-degrading bacteria were isolated, purified and tested for their enzymes activity and the results were compared to the enzymes activity of the anaerobic bacteria namely Clostridium acetobutylicum and Clostridium butyricum strains using the Dinitrosalicylic Acid (DNS) method. The aerobic strain HBI classified under the genus Bacillus produced the highest glucose concentration of 34.76 mg/dL after 72 hours of incubation at 37 degrees C with carboxymethycellulose (CMC) as the only carbon source in the media. The results of this study suggest that enzymes activity in both aerobic and anaerobic environments decreases with increasing incubation time -- Author's abstract.